IMPLMENTASI KEBIJAKAN PENYALURAN BEASISWA ANAK ASUH EKS LOKALISASI DINAS SOSIAL KOTA SURABAYA - Endang Setyowati; Nabilatun Nafisah; Shinta Olivia Virnanda (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2026)
The Foster Child Scholarship Program for Former Localization Areas has been running for quite a long time, but in the implementation of the program it is necessary to conduct an assessment to determine how the policy is implemented and the factors that influence its success. This program was created as a form of compensation by the Surabaya City Government for communities affected by the closure of localization areas. This study aims to analyze the distribution process of the Former Localization Scholarship and whether it has been effective for the community. This study uses a descriptive qualitative method by conducting in-depth interviews with the Social Service, recipients of the Former Localization Scholarship, observations, and documentation, as well as factual information analysis regarding the form of the policy implementation process of the Former Localization Scholarship in Surabaya. The results of the study indicate that the implementation of the Foster Child Scholarship Distribution Policy for Former Localization Areas at the Surabaya City Social Service has been carried out well; the program has clear targets and has been able to provide benefits for the beneficiaries. This study still found several obstacles in policy implementation, such as the limited understanding of some community members regarding the program mechanism, the utilization of assistance that has not been entirely in accordance with educational purposes, as well as the diverse social and economic conditions of the beneficiaries' families. This program no longer accepts new beneficiaries and only continues the policies that have been implemented previously, therefore it is important to examine the implementation of the policy in its execution.